2016
DOI: 10.1152/ajpregu.00044.2016
|View full text |Cite
|
Sign up to set email alerts
|

The ghrelin receptor agonist HM01 mimics the neuronal effects of ghrelin in the arcuate nucleus and attenuates anorexia-cachexia syndrome in tumor-bearing rats

Abstract: The gastric hormone ghrelin positively affects energy balance by increasing food intake and reducing energy expenditure. Ghrelin mimetics are a possible treatment against cancer anorexia-cachexia syndrome (CACS). This study aimed to characterize the action of the nonpeptidergic ghrelin receptor agonist HM01 on neuronal function, energy homeostasis and muscle mass in healthy rats and to evaluate its possible usefulness for the treatment of CACS in a rat tumor model. Using extracellular single-unit recordings, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 51 publications
4
30
0
Order By: Relevance
“…In rats, ghrelin treatment suppresses the cachectic weight loss induced by human melanoma cancer cell implantations [109]. Improved food intake and prevention of tissue wasting has further been observed upon ghrelin treatment in a mouse model of lung cancer-induced cachexia [110], as well as in a series of studies evaluating the role of ghrelin and its analogs in rodent tumor-bearing models of cachexia [108,111,112,113,114]. In line with these data, ghrelin stimulates feeding and lean body mass accrual in a rat model of chronic kidney disease-induced cachexia [115], attenuates cachexia in rats with heart failure [116], inhibits skeletal muscle breakdown after burn injury in rats [117] and inhibits angiotensin II-induced cachexia in mice [118].…”
Section: Anorexia/cachexiamentioning
confidence: 99%
“…In rats, ghrelin treatment suppresses the cachectic weight loss induced by human melanoma cancer cell implantations [109]. Improved food intake and prevention of tissue wasting has further been observed upon ghrelin treatment in a mouse model of lung cancer-induced cachexia [110], as well as in a series of studies evaluating the role of ghrelin and its analogs in rodent tumor-bearing models of cachexia [108,111,112,113,114]. In line with these data, ghrelin stimulates feeding and lean body mass accrual in a rat model of chronic kidney disease-induced cachexia [115], attenuates cachexia in rats with heart failure [116], inhibits skeletal muscle breakdown after burn injury in rats [117] and inhibits angiotensin II-induced cachexia in mice [118].…”
Section: Anorexia/cachexiamentioning
confidence: 99%
“…GSK 894281 is an orally bioavailable BBB-penetrant ghrelin agonist which causes a prompt and dose-related output of faecal pellets after administration [326]. HM01 is another such agonist in preclinical trials as a colokinetic; again, its prokinetic action is attributed to its ability to cross the BBB and act on GHSR-1a’s present in the nerves of the lumbar section of the spinal cord [327,328,329,330]. …”
Section: Ghrelin and Ghrelin Ligands: Pharmacokinetic Perspectivesmentioning
confidence: 99%
“…Given the orexigenic action of ghrelin [9,14,37] and ghrelin agonists [27,28,38] in rodents, it was unexpected that HM01 did not induce a clear increase in food intake in NTB animals, although HM01-treated mice consumed slightly more food in the first few days of treatment [27]. Therefore, the increase in body weight appears to be mediated by other mechanisms than increased energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin is thought to counteract muscle degradation by IGF-1-dependent inhibition of proteolytic factors such as the E3 ubiquitin ligases muscle RING-finger protein-1 (MuRF-1) and muscle atrophy F-box (MAFbx)/atrogin-1 [12]. Although previous human clinical trials [23,24,25] and studies in rodent cancer models [26,27,28,29,30,31] confirmed therapeutic effectiveness of ghrelin or ghrelin analogues as anti-CACS treatment, currently no ghrelin-based drug is approved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation